2016
DOI: 10.1890/15-0793.1
|View full text |Cite
|
Sign up to set email alerts
|

Local differences in parasitism and competition shape defensive investment in a polymorphic eusocial bee

Abstract: Many colonial animals rely for their defense on a soldier caste. Adaptive colony demography theory predicts that colonies should flexibly adjust the investment in different worker castes depending on the colony needs. For example, colonies should invest more in defensive workers (e.g., soldiers) in dangerous environments. However, evidence for this prediction has been mixed. We combined descriptive and experimental approaches to examine whether defensive investment and worker size are adjusted to local ecology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 54 publications
0
17
0
1
Order By: Relevance
“…Lestrimelitta bees pose a threat to many Neotropical species as robbers of resources 29 and are suspected to be the driving force behind the evolution of soldiers in T. angustula 9,16 . For example, T. angustula soldiers aggressively attack objects that chemically or visually resemble robber bees 35 and colonies have more soldiers in areas where Lestrimelitta attacks are more common 16 . Ten of the 28 studied species are known victims of Lestrimelitta, whose attacks frequently destroy colonies 29 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lestrimelitta bees pose a threat to many Neotropical species as robbers of resources 29 and are suspected to be the driving force behind the evolution of soldiers in T. angustula 9,16 . For example, T. angustula soldiers aggressively attack objects that chemically or visually resemble robber bees 35 and colonies have more soldiers in areas where Lestrimelitta attacks are more common 16 . Ten of the 28 studied species are known victims of Lestrimelitta, whose attacks frequently destroy colonies 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In stingless bees, the emergence of dangerous robbers and an environment that favored the storage of valuable resources might represent two important incentives for having larger and, therefore, stronger entrance guards. Previous studies have shown that a more dangerous environment can lead to increased investment in colony defence in species that already have soldiers 16,40 . Our study extends this theme and identifies a specific threat ( Lestrimelitta robber bees) as a possible selective force for the evolution of new sub-castes and increased social complexity in Neotropical stingless bees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uma reserva de soldados poderia levar a um sistema social resistente, que deveria evoluir quando o ambiente biótico contém ameaças potencialmente catastróficas ). Segers et al (2016), demonstraram que colônias que não estão expostas a ameaças podem apresentar menor quantidade de guardas em sua entrada. Característica que corrobora com a teoria de eficiência ergonômica (Oster & Wilson, 1978).…”
Section: Discussionunclassified